Skills and labour market performance in Sweden - Bussi, Margherita (OECD Publishing, 2015)
Both educational attainment and skills, as measured in the OECD Survey of Adult Skills (PIAAC), are high in Sweden. They are not perfect substitutes, but both are to some degree necessary for successfully integrating in the Swedish labour market. This paper describes the distribution of proficiency in literacy in the population and explores its determinants, and uncovers a strong relationship between literacy and the likelihood of being employed. The relationship between proficiency in literacy and the likelihood of participating in adult education is also explored. Lower employment prospects for immigrants are well explained by lower literacy proficiency, lower education and less favourable socio-economic backgrounds. This Working Paper relates to the 2015 OECD Economic Survey of Sweden www.oecd.org/eco/surveys/economic-survey-sweden.htm
Keywords: Economics; Sweden